VAULTING TUBE PRODUCTION IN DACIA MEDITERRANEA: A CASE STUDY FROM THE STRYMON VALLEY IN ITS REGIONAL CONTEXT - Alexander K. Harizanov (Journal of Ancient History and Archaeology)
In 2017 a new Late Roman settlement was discovered on the road bed of the Struma Highway, near the modern day village of Moshtanets, Blagoevgrad district. The archaeological site was located on a slope and adjacent river terrace, close to the right bank of the Struma River (ancient Strymon). During the excavations, a ceramic kiln and a deposit of ceramic tubes were discovered in its southern sector. This contribution is aimed at presenting both the kiln and the finds, identified as terracotta vaulting tubes (tubi fittili). The latter are described and analysed in the context of similar artefacts from the northern half of the Balkans, and especially from within the Late Roman province of Dacia Mediterranea. In conclusion, some observations are made concerning the purpose and possible recipients of these locally made products.